Functional characterization and therapeutic potential of human umbilical cord blood mononuclear cells - Yu Zhang; Yueda Lu; Xinyue Hu; Mengxing Jiang; Zhixiu Chen; Lingkun Jin; Min Li; Chen Chen; Jianye Wang (Regenerative Therapy)
Human umbilical cord blood mononuclear cells (hUCB-MNCs) are a population of cells derived from neonatal cord blood, encompassing various stem cells and immune cells. The unique characteristics of hUCB-MNCs endow them with distinctive multifunctionality, including the promotion of angiogenesis, acceleration of tissue repair, regulation of immune responses, neuroprotection, alleviation of inflammatory reactions, enhancement of antioxidant capacity, reduction of fibrosis processes, and inhibition of apoptosis. These diverse biological properties underscore the significant clinical therapeutic potential of hUCB-MNCs, which are widely applied in the treatment of various diseases. This review aims to summarize the underlying mechanisms responsible for the multifunctional attributes of hUCB-MNCs, elucidating their potential modes of action in disease management and providing novel theoretical insights and practical guidance for their expanded application across different disease domains. By synthesizing current research findings, this review may provide insights into the potential clinical applications of hUCB-MNCs in the fields of regenerative medicine and cell therapy.